Prevalence of atypical Leptospira serovars in New Zealand’s pastoral livestock - Mannewald, Alice (SLU/Dept. of Clinical Sciences (until 231231), 2016)
The aim of this study was to estimate the overall prevalence and herd/flock seroprevalence of the Leptospira serovars Ballum, Copenhageni and Tarassovi and the differences in prevalence between regions in New Zealand. The samples used in the study were 3,878 stored serum samples from beef cattle, deer and sheep. The samples came from 9 different regions and from both the North Island and the South Island. The samples were analysed by MAT (microscopic agglutination test) using the titre cut-off point 1:48. Seroprevalence in beef cattle were 13.7%, 14.7% and 18.0% for Ballum, Copenhageni and Tarassovi, respectively. In deer the corresponding figures were 6.6%, 15.5% and 3.6% and in sheep 10.5%, 16.7% and 14.0%. When a farm was regarded as positive as long as at least one positive animal was found, the prevalence of farms positive for Ballum was 76.0% and 88.4% for Copenhageni and 74.0% for Tarassovi. Two farms had no positive samples for any of the three serovars. The prevalence of the three serovars could also been seen to vary between the different regions, although there was a huge difference in number of samples from the regions. Ballum seemed to have a lower prevalence in the South Island than in the North Island. The origin of these serovars is unknown. Based on earlier findings, however, a working hypothesis for future studies is that domestic livestock may be infected through contact with infected wildlife species. As serovars Tarassovi and Ballum are not included in any of the vaccines registered in New Zealand, this study demonstrated that vaccination cannot fully protect farmers against exposure to Leptospira.